THE ILLOCUTIONARY ACTS OF LUFFY’S UTTERANCES TO HIS ADDRESSEES IN COMIC ONE PIECE - Adhy Kurnia Putra Fasril; Bachtiar Bachtiar (State University of Medan, 2012)
Abstract One aim of this article is to show through a concrete example how illocutionary acts used in One Piece comic. The illustrative example is taken from the utterances of One Piece comic. Central to the analysis proper form of utterances in One Piece comic that contain of illocutionary acts; i.e. representative, directive, commissive, expressive, declarative. 90 utterances were interpreted by actor, and it was found that the use of iilocutionary acts. Keywords: Comic One Piece, Luffy’s Utterances, Illocutionary Acts